Kualitas Pelayanan Penyelenggaraan Pelayanan Perizinan di Dinas Penanaman Modal dan Pelayanan Terpadu Satu Pintu (DPMPTSP) Jawa Timur - Putri Indah Sari; Meirinawati M; Eva Hany Fanida; Trenda Aktiva Oktariyanda (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
The provision of business licensing services constitutes a crucial pillar in strengthening the investment ecosystem and accelerating economic growth at the regional level. In East Java, e-government innovation is implemented through the East Java Online Single Submission (JOSS) system under the authority of the Department of Investment and One-Stop Integrated Services (DPMPTSP). However, its operation still faces obstacles such as lengthy processing times, complex bureaucracy, and weak synergy among technical agencies. This study aims to evaluate the quality of licensing services on the JOSS platform at DPMPTSP East Java. Using a descriptive qualitative approach, data were collected through observation, interviews, and document review. The evaluation framework refers to the theory of Pham et al. (2023), which examines five main aspects: ease of interaction, service fulfillment, user care, data security, and trust. The research findings indicate that, in general, the JOSS platform has facilitated access to licensing services fairly effectively. Although aspects of security and ease of use are adequate, the variables of timeliness (fulfillment) and complaint handling (citizen care) still require improvement. Synchronization among agencies and enhancement of human resource quality are key to optimizing services in the future.